Evaluating agro-meteorological disaster of China based on differential evolution algorithm and VIKOR - Yu, Xiaobing; Lu, Yiqun; Cai, Mei (Natural hazards (Dordrecht), 2018)
Agriculture is not only concerned with the daily life of the local residents, but also plays a significant role in the sustainable development of China and even the stability of the world grain market. The evaluation of meteorological disaster involves many indexes; it can be regarded as a multiple criterion decision-making problem. Comprehensive indexes system of agro-meteorological disaster is proposed. The relative weights of the indexes are acquired by differential evolution algorithm. A novel evaluation model based on VIKOR is proposed to estimate the agro-meteorological disaster of China from 2006 to 2010. The experiment results have demonstrated that the situation of agro-meteorological disaster in North and Northwest area of China was severe and the agro-meteorological disaster of 2008 was very serious.